2010
DOI: 10.1136/bjo.2009.164616
|View full text |Cite
|
Sign up to set email alerts
|

Use of the light-adjustable lens to correct astigmatism after cataract surgery

Abstract: The LAL can be adjusted postoperatively to correct residual astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 9 publications
1
20
0
2
Order By: Relevance
“…When the appropriate power adjustment is achieved, the entire IOL is irradiated in a second lock-in procedure to consume unreacted macromers in the lens. 85 In a series of small pilot studies published in 2009 and 2010, Chayet et al [88][89][90] demonstrated the efficacy and predictability of the Calhoun light-adjustable IOL across a range of refractive circumstances. In a prospective study of 14 eyes of 14 patients with a mean age of 63 years, light-adjustable IOLs were purposefully implanted to leave between À0.25 D and À1.50 D of residual myopia.…”
Section: Light-adjustable Intraocular Lensmentioning
confidence: 97%
See 1 more Smart Citation
“…When the appropriate power adjustment is achieved, the entire IOL is irradiated in a second lock-in procedure to consume unreacted macromers in the lens. 85 In a series of small pilot studies published in 2009 and 2010, Chayet et al [88][89][90] demonstrated the efficacy and predictability of the Calhoun light-adjustable IOL across a range of refractive circumstances. In a prospective study of 14 eyes of 14 patients with a mean age of 63 years, light-adjustable IOLs were purposefully implanted to leave between À0.25 D and À1.50 D of residual myopia.…”
Section: Light-adjustable Intraocular Lensmentioning
confidence: 97%
“…Finally, in a small prospective study of 5 patients with a mean age of 68 years and cylinder ranging from 1.25 to 1.75 D, Chayet et al 90 looked at the lightadjustable IOL's performance in correcting astigmatism. All patients achieved an SE refraction within G0.25 D of emmetropia and a UDVA of 20/25 or better at the 9-month follow-up; no patient lost CDVA.…”
Section: Light-adjustable Intraocular Lensmentioning
confidence: 98%
“…изучали возможность использования light-adjustable ИОЛ для коррекции астигматизма [32]. Во всех случаях достигну-та SE рефракция в пределах ±0,25 Дптр от эмметропии, НКОЗ 0,8 и выше через 9 месяцев после процедуры, ни в одном случае не отмечали потери МКОЗ [32].…”
Section: светорегулируемые (Light-adjustable) иолunclassified
“…[6][7][8] Despite this techniques, toric IOL implantation seems very successful and predictable to correct moderate and especially high degree astigmatism. 9,10 With the widespread use of toric IOLs, the researchers needed to evaluate prevalence of astigmatism in their countries.…”
Section: Age Groups (Years)mentioning
confidence: 99%